2018
DOI: 10.1364/ao.57.000c56
|View full text |Cite
|
Sign up to set email alerts
|

Acousto-optic visualization of optical wavefronts [Invited]

Abstract: The paper presents a short survey on theoretical and experimental investigations of an acousto-optic (AO) method of optical wavefront visualization proposed and developed at Moscow State University. The method is based on angular selectivity of Bragg diffraction. It is shown that distribution of light intensity in the visualized image is proportional to the phase gradient in the AO interaction plane. Spatial resolution and contrast of the visualized image are determined primarily by the divergence angle of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is the most common AOTF type, widely available and used in various hyperspectral imaging experiments [11,12]. Several previous applications of AO devices for optical image processing include image edge enhancement in coherent light [13][14][15][16][17][18][19][20] and phase imaging [21][22][23]. Novel designs of optical traps based on LBS by an AOSF have been recently demonstrated by Obydennov et al [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This is the most common AOTF type, widely available and used in various hyperspectral imaging experiments [11,12]. Several previous applications of AO devices for optical image processing include image edge enhancement in coherent light [13][14][15][16][17][18][19][20] and phase imaging [21][22][23]. Novel designs of optical traps based on LBS by an AOSF have been recently demonstrated by Obydennov et al [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…S. Case was the first, to the best of our knowledge, to demonstrate optical edge extraction using Bragg processing [3] . Balakshy pointed out the possibility of using acousto-optic interaction to perform spatial filtering in 1984 and recently presented a short survey on the use of acousto-optics for optical wavefront visualization [6,7] . Xia et al for the first time, to the best of our knowledge, demonstrated experimental Bragg diffraction image edge extraction and pioneered image processing in an imaging system with an acousto-optic modulator (AOM) as a programmable volume hologram [8] .…”
Section: Introductionmentioning
confidence: 99%
“…As the research of acousto-optic theory continues to progress, the principles of isotropic and anisotropic acousto-optic interactions need to be unified. We can consider the acousto-optic effect as a parametric interaction process, which is described by the relationship between the nonlinear polarization vector and the strain [6][7][8].…”
Section: Introductionmentioning
confidence: 99%